2011
DOI: 10.1371/journal.pone.0021004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of a New Immunomodulatory Protein from Anoectochilus formosanus which Induces B Cell IgM Secretion through a T-Independent Mechanism

Abstract: An immunomodulatory protein (IPAF) was purified and cloned from Anoectochilus formosanus, an Orchidaceae herbal plant in Asia. The major targeting immune cells of IPAF and its modulating effects toward B lymphocytes were investigated. Rapid amplification of cDNA ends (RACE) was conducted to clone the IPAF gene, and the obtained sequence was BLAST compared on the NCBI database. MACS-purified mouse T and B lymphocytes were stimulated with IPAF and the cell proliferation, activation, and Igs production were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…These data indicated that IPAF activated murine macrophages through TLR4-dependent NF-κB activation. Intriguingly, the IPAF-induced B cell activation was not qualitatively affected by TLR4 deficiency [9]. This implied that TLR4 might participate partially in the interaction between IPAF and B cells, and that other receptors such as the B cell receptor might be involved in the IPAF-induced B cell activation.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…These data indicated that IPAF activated murine macrophages through TLR4-dependent NF-κB activation. Intriguingly, the IPAF-induced B cell activation was not qualitatively affected by TLR4 deficiency [9]. This implied that TLR4 might participate partially in the interaction between IPAF and B cells, and that other receptors such as the B cell receptor might be involved in the IPAF-induced B cell activation.…”
Section: Discussionmentioning
confidence: 90%
“…The IPAF used in this study was prepared as described in our previous work [9]. Briefly, the whole plant of A. formosanus was homogenized by sonication, and the crude protein was precipitated by applying 90% of ammonium sulfate.…”
Section: Preparation Of Ipafmentioning
confidence: 99%
See 1 more Smart Citation
“…), de novo contig assembly was performed by combining the processed-reads based on sequence overlap. To identify the gene encoding YZP, the contigs were translated into protein sequences, which were subsequently matched to the N-terminal amino acid sequence of the YZP derived using previously described methods [15]. The YZP gene was PCR-cloned using primers designed based on the sequence of the contig encoding the N-terminus of YZP (Table S1 and Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…Mice splenic cells were acquired as previously described [15]. Briefly, the spleens were excised from euthanized mice, and the total splenocytes and splenic CD19 + B cells or CD90 + T cells were purified using MACS system (Miltenyi Biotec, Bergisch Gladbach, Germany).…”
Section: Methodsmentioning
confidence: 99%